2013
DOI: 10.1155/2013/421205
|View full text |Cite
|
Sign up to set email alerts
|

Low Rate of Detection of Mucosal High-Risk-Type Human Papillomavirus in Korean Patients with Extragenital Bowen's Disease and Squamous Cell Carcinoma, Especially in Digital Cases

Abstract: Human papillomavirus (HPV) infection has been demonstrated in some of the nonmelanoma skin cancers as well as in precancerous lesions. Multiple infections of mucosal high-risk HPV may contribute to the onset of digital Bowen's disease through, if any, digital-genital transmission. We screened for the presence of the mucosal HPV DNA in patients with extragenital Bowen's disease (n = 30), squamous cell carcinoma (n = 11), bowenoid papulosis (n = 9), verrucous carcinoma (n = 1), actinic keratosis (n = 5), and bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…In our set of HPV-positive BD specimens, the β-papillomavirus genotypes predominated over α-papillomavirus genotypes, which is consistent with previous reports on BD/carcinoma in situ in both immunocompetent and immunocompromised patients [ 5 – 8 , 16 , 42 , 43 ]. Nevertheless, α-HPV genotypes were detected in significant proportion of BD lesions (~10 % of all BD lesions and ~29 % of HPV-positive BD lesions), which is in line with seven previous studies that examined the presence of only α-HPV genotypes in BD and reported in average 14.7 % of the HPV-positive BD cases (range 4.8–39 %) [ 13 , 15 , 23 , 24 , 45 47 ].…”
Section: Discussionsupporting
confidence: 89%
“…In our set of HPV-positive BD specimens, the β-papillomavirus genotypes predominated over α-papillomavirus genotypes, which is consistent with previous reports on BD/carcinoma in situ in both immunocompetent and immunocompromised patients [ 5 – 8 , 16 , 42 , 43 ]. Nevertheless, α-HPV genotypes were detected in significant proportion of BD lesions (~10 % of all BD lesions and ~29 % of HPV-positive BD lesions), which is in line with seven previous studies that examined the presence of only α-HPV genotypes in BD and reported in average 14.7 % of the HPV-positive BD cases (range 4.8–39 %) [ 13 , 15 , 23 , 24 , 45 47 ].…”
Section: Discussionsupporting
confidence: 89%
“…However, the reported prevalence of HPV in extragenital BD ranges 0-83%, and thus it is not clear to what extent HPV is involved in the pathogenesis of extragenital BD. [5][6][7][8][9][10][11][12][13][14] In this study, to determine the prevalence of HPV in BD, we examined 142 consecutively diagnosed (at our department) BD lesions for the mucous-type HPV. As a previous study showed that the use of a single PCR primer set for HPV detection is likely to underestimate the incidence of HPV-positive cancers, 27 we performed the PCR reactions using three different primer sets (GP5+/6+, L1C1/C2 and MY09/11) located in the L1 open reading frame.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Recently, cases of extragenital BD associated with mucous types of HPV also have been reported. [5][6][7][8][9][10][11][12][13][14] However, the detection rate of HPV in BD has varied among all reports, probably depending on the population studied and the sensitivity and specificity of the method used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Available data on viral prevalence and type spectrum in these tumours are highly variable. Some studies show detection rates of mucosal HR-HPV in up to 90% (1)(2)(3)(4)(5), while others fail to detect viral DNA (6,7). Viral presence is reported to be confined to tumours on peri-and subungual sites, or predominantly on proximal phalanges rather than ungual sites (2,3).…”
mentioning
confidence: 99%